2022
DOI: 10.1016/j.jimonfin.2021.102511
|View full text |Cite
|
Sign up to set email alerts
|

A panel VAR analysis of macro-financial imbalances in the EU

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
0
8
1
Order By: Relevance
“…current account imbalances. 5 Similarly, using a Bayesian panel VAR approach on 27 economies over the 1994-2012 period, Comunale (2021) studied the interaction among RER misalignment, current account misalignment, and financial gaps in the EU. Comunale observed that RER misalignment shocks had a negative impact on financial and output gaps, where RER misalignment could, in turn, be affected by current account misalignment shocks.…”
Section: B Real Exchange Rate Misalignment and The Business Cyclementioning
confidence: 99%
“…current account imbalances. 5 Similarly, using a Bayesian panel VAR approach on 27 economies over the 1994-2012 period, Comunale (2021) studied the interaction among RER misalignment, current account misalignment, and financial gaps in the EU. Comunale observed that RER misalignment shocks had a negative impact on financial and output gaps, where RER misalignment could, in turn, be affected by current account misalignment shocks.…”
Section: B Real Exchange Rate Misalignment and The Business Cyclementioning
confidence: 99%
“…Various authors have been studied interactions among current account balance and real exchange rate [8,9]. In particular [9] has applied a panel VAR analysis to 27 EU members over the period 1994-2012 and has found that the increase in a current account imbalance causes an expansion of real exchange rate misalignment and thus lowering competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various authors have been studied interactions among current account balance and real exchange rate [8,9]. In particular [9] has applied a panel VAR analysis to 27 EU members over the period 1994-2012 and has found that the increase in a current account imbalance causes an expansion of real exchange rate misalignment and thus lowering competitiveness. However, author [9] does not report the number of instruments, which in case of T = 19 can not be less than N = 27 when applying standard GMM-style estimator to the homogeneous PVAR model [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The term «macrofinancial» is used not only in the context of security, but also in other contexts, namely: «macrofinancial disproportions» [1], «macrofinancial stability» [2], «macrofinancial analysis» [3], etc. The activity of using these terms increased after the global financial crisis of 2008-2010.…”
mentioning
confidence: 99%